2023
DOI: 10.47836/pjst.31.3.01
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid-Amended Formulation Improves Shelf-Life of Plant Growth-Promoting Rhizobacteria (PGPR) Under Laboratory Conditions

Abstract: Plant growth-promoting rhizobacteria (PGPR) is a soil bacterium that positively impacts soil and crops. These microbes invade plant roots, promote plant growth, and improve crop yield production. Bacillus subtilis is a type of PGPR with a short shelf-life due to its structural and cellular components, with a non-producing resistance structure (spores). Therefore, optimum formulations must be developed to prolong the bacterial shelf-life by adding humic acid (HA) as an amendment that could benefit the microbes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Arriel-Elias et al ( 2018) studied an experiment and concluded that a formulation containing glycerol, PVP, and molasses effectively boost the growth of bacterial strain species Pseudomonas fluorescens and Burkholderia pyrrocinia formulation throughout a 180-day shelf-life experiment, which demonstrates the effectiveness microbial activity pattern in the current study. A progressive increase in microbial activity was observed in a study conducted by Buraq et al (2023), that cell protectants such as humic acid significantly prolonged the plant growthpromoting bacterial shelf-life with minimal cell loss. The decrease in dissolved oxygen is due to increased O 2 demand for culture growth.…”
Section: Amendmentsmentioning
confidence: 97%
“…Arriel-Elias et al ( 2018) studied an experiment and concluded that a formulation containing glycerol, PVP, and molasses effectively boost the growth of bacterial strain species Pseudomonas fluorescens and Burkholderia pyrrocinia formulation throughout a 180-day shelf-life experiment, which demonstrates the effectiveness microbial activity pattern in the current study. A progressive increase in microbial activity was observed in a study conducted by Buraq et al (2023), that cell protectants such as humic acid significantly prolonged the plant growthpromoting bacterial shelf-life with minimal cell loss. The decrease in dissolved oxygen is due to increased O 2 demand for culture growth.…”
Section: Amendmentsmentioning
confidence: 97%